PEMBERLAKUAN KONSEP HUKUM YANG HIDUP BAGIAN DARI HUKUM ADAT DALAM PERKEMBANGAN KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL DI INDONESIA - Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2025)
Living law is part of customary law in Indonesia. Customary law is the original law of the Indonesian people. However, in some views, both from academics and practitioners, there are still differences in understanding regarding the application of existing laws in Indonesia. The method in this research uses the normative legal research method. Where the results of the discussion present an analysis between legal theory and legal formulation, especially those related to legal provisions that exist in customary law provisions and laws that exist in the provisions of the formulation of the principle of material legality. The results of this study state that in the development of criminal law reform in Indonesia, written law is highly respected in law enforcement in Indonesia as stipulated in the principles of formal legality so that the original Indonesian law, in this case customary law, has been neglected in Indonesia. However, with the legal reforms in the National Criminal Code, living law or customary law has now been given scope in the formulation of Article 2 of the National Criminal Code, so that in the enforcement of criminal law in Indonesia today, there is directly an idea of ​​balance between the principle of formal legality and the principle of material legality. So it is hoped that in the future, with the implementation of the National Criminal Code, law enforcement in Indonesia will be able to provide law enforcement that contains the values ​​of justice, benefit and certainty. Keywords; The principle of material legality, customary law, criminal law.